2002
DOI: 10.1161/01.atv.0000027524.86752.02
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Properties of Extracellular Superoxide Dismutase

Abstract: Objective-The cytosolic form of Cu/Zn-containing superoxide dismutase (SOD1) has peroxidase activity, with H 2 O 2 used as a substrate to oxidize other molecules. We examined peroxidase properties of the extracellular form of SOD (SOD3), a major isoform of SOD in the vessel wall, by using recombinant SOD3 and an in vivo model of atherosclerosis. Methods and Results-In the presence of HCO 3 Ϫ , SOD3 reacted with H 2 O 2 to produce a hydroxyl radical adduct of the spin trap 5-diethoxyphosphoryl-5methyl-1-pyrroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 45 publications
6
133
2
4
Order By: Relevance
“…This finding, in conjunction with the hyperoxia-induced increase in lung H 2 O 2 observed solely in females, strongly suggests that the reduced thromboxanemediated force development in the pulmonary arteries reflects dismutation of the excess superoxide by SOD. Despite the published evidence that H 2 O 2 can inactivate SOD3 (27), our data on hyperoxia-exposed female pups suggest otherwise. This apparent discrepancy might be related to the fact that although the lung H 2 O 2 content was increased, the levels measured in the present experiments are significantly lower than those required for SOD inactivation, as previously reported (27).…”
Section: Oxygen and Newborn Pulmonary Vasculaturecontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding, in conjunction with the hyperoxia-induced increase in lung H 2 O 2 observed solely in females, strongly suggests that the reduced thromboxanemediated force development in the pulmonary arteries reflects dismutation of the excess superoxide by SOD. Despite the published evidence that H 2 O 2 can inactivate SOD3 (27), our data on hyperoxia-exposed female pups suggest otherwise. This apparent discrepancy might be related to the fact that although the lung H 2 O 2 content was increased, the levels measured in the present experiments are significantly lower than those required for SOD inactivation, as previously reported (27).…”
Section: Oxygen and Newborn Pulmonary Vasculaturecontrasting
confidence: 99%
“…Despite the published evidence that H 2 O 2 can inactivate SOD3 (27), our data on hyperoxia-exposed female pups suggest otherwise. This apparent discrepancy might be related to the fact that although the lung H 2 O 2 content was increased, the levels measured in the present experiments are significantly lower than those required for SOD inactivation, as previously reported (27).…”
Section: Oxygen and Newborn Pulmonary Vasculaturecontrasting
confidence: 99%
“…This finding could indicate compensation of the oxidative stress caused by CVD and CKD (111). The antioxidant activity of uric acid could be mediated by increasing the activity of SOD1 and SOD3 (62). Others have suggested that uric acid only functions as an antioxidant in the extracellular space, and indeed a reciprocal relationship has been demonstrated between uric acid and NO level in serum (79).…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 91%
“…(eNOS) uncoupling and endothelial dysfunction (121,145). Although elevated levels of uric acid may confer protective antioxidant effects on the vasculature and the kidneys, the correlation with cardiovascular disease risk is not readily apparent (145).…”
Section: Nistala Et Al 2052mentioning
confidence: 99%